Weaker Plant‐Frugivore Trait Matching Towards the Tropics and on Islands - Huang, Xiao; Dalsgaard, Bo; Chen, Si‐Chong (Ecology letters, 2025)
ABSTRACT Biotic interactions play an important role in species diversification and maintenance and, thus, are regarded as the architecture of biodiversity. Since Darwin and Wallace, biologists have debated whether biotic interactions are stronger towards the tropics and on continents, when compared to temperate regions and islands. Here, based on 354 avian frugivory networks accounting for 22,199 interactions between 1247 bird species and 2126 plant species, we quantified trait matching strength, which reflects interaction strength and specificity, across gradients of latitude and insularity globally. We found that matching between beak size and fruit size was significantly stronger towards the poles and on continents, when compared with the tropics and on islands. As underlining ecological factors, trait matching was stronger with a larger proportion of frugivory (measured as the mean proportion of fruits in bird diets) and network‐level mean beak size, and with a smaller proportion of fleshy‐fruited species (measured as the proportion of fleshy‐fruited plant species in the botanical country where the network was located). These findings suggest that the latitudinal and insular patterns in trait matching are driven by biotic factors that may relate to trait co‐evolution between interacting species and optimal foraging for bird species. This study investigates beak‐fruit size matching in frugivory to understand the strength of biotic interactions globally. Analysing 354 avian frugivory networks across different latitudes and insularity, the study finds that beak‐fruit size matching is stronger at higher latitudes and on continents compared to lower latitudes and islands. These results support Darwin's hypothesis that biotic interactions are weaker on islands but challenge Wallace's view that interactions are stronger in the tropics, with implications for ecological and evolutionary theories on global biodiversity patterns.